Pengaruh financial literacy, locus of control, income, hedonism lifestyle dan optimism terhadap financial behavior generasi milenial - Irbatul Umniyyah (Jurnal Ilmu Manajemen, 2023)
The existence of the Covid-19 outbreak in 2019 made people have a habit of shopping online through marketplace platforms, which made people have very consumptive and apprehensive financial behavior. This study aims to identify and analyze the influence of financial literacy, locus of control, income, hedonism lifestyle, and optimism on financial behavior. The object of this study is the millennial generation with an age range of 26-41 years who live in Surabaya and who are already working and have income. The research method used is the quantitative research method with multiple linear regression analysis. The number of samples collected was 220 respondents using purposive sampling by distributing questionnaires online. Based on the t-test, the results showed a partial influence between locus of control, hedonism lifestyle, and optimism on financial behavior. However, there is no influence between financial literacy and income on financial behavior. Therefore, the millennial generation needs to increase self-control and a sense of optimism and reduce their hedonic lifestyle so that they can manage their finances properly and wisely according to their needs. Therefore the millennial generation in Surabaya is expected to improve their locus of control and optimism in themselves so that they can manage finances wisely by controlling their finances so that he does not have a hedonistic lifestyle that worsens financial management.